2017
DOI: 10.1200/jgo.2016.005629
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Human Papillomavirus Self-Sampling for Cervical Cancer Screening in an Indigenous Community in Guatemala

Abstract: PurposeCervical cancer rates in Latin America are higher than those in developed countries, likely because of the lower prevalence of screening. Specifically, less than 40% of women in Guatemala are regularly screened and even fewer women are screened in indigenous communities. Current screening strategies—Pap smears and visual inspection with acetic acid—might not be the most effective methods for controlling cancer in these settings. We thus investigated the potential of self-collection of cervical samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
62
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 34 publications
(39 reference statements)
13
62
1
1
Order By: Relevance
“…It is unclear whether it can be scaled up to cover a whole population. Thus, there is still considerable discussion on the most effective strategies for managing HPV+ women in different economic and cultural settings (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether it can be scaled up to cover a whole population. Thus, there is still considerable discussion on the most effective strategies for managing HPV+ women in different economic and cultural settings (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of self-collection in low-and middleincome countries (LMIC) have not evaluated actual patient preferences, as measured by screening adherence. Rather, studies in LMICs have had enrolled, consenting women undergo self-collection with or without also getting a provider-collected specimen and then relied on questionnaires and interviews to understand the acceptability/ patient preferences for self-collection (11)(12)(13)(14). As an exception, in a randomized trial of almost 6,000 women in Argentina, women offered self-collected sampling were 4-fold more likely to complete screening compared with those who were offered clinic-based provider-collected sampling for cytology (86% vs. 20%, respectively; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Winer [4] 2016 A significant proportion of Hopi women have low adherence to screening 62% of women prefer self-sampling Easy method that allows them to get privacy and comfort Convenient method in terms of time saving and compatibility with daily activities Self-sampling is a workable and acceptable method Broquet [3] 2015 Acceptability of self-sampling for HPV testing was equally excellent in both groups (urban and rural), despite its difference in sociodemographic factors and knowledge of cervical cancer The population has not been screened for at least 3 years for the following reasons: ashamed to be examined by a male doctor, no symptoms at all, belief that testing was not necessary, long waiting time at clinics, belief in pain associated with testing and fear of abnormal results In addition, it is also noted that in this population of untracked women, there is a lack of trust in the health system There was little knowledge and early knowledge about HPV and cervical cancer However, to be efficiently and successfully implemented, a screening program must combine technical qualities and cost-effectiveness with education of the women at risk of developing cervical carcinoma, with clear and straightforward elucidation about HPV biology, stressing the importance of screening adherence to prevent cancer [10,18]. Despite the importance of education, about half of the studies reviewed show that women have a significant lack of knowledge about HPV and the screening test: for example, Gottschlich et al [23], who found that only 15% of indigenous women in Guatemala included in the study had some knowledge of HPV. The tables generated in this review point to some facts to be taken into account when evaluating the performance of self-harvesting material.…”
Section: Discussionmentioning
confidence: 99%
“…(14) Were the main potential confounders measured and statistically adjusted for their impact on the relationship between exposure and outcome? [3] moderate to high Possati-Resende [10] moderate to high Haguenoer [1] high Allende [19] moderate to high Maza [11] moderate to high Esber [9] moderate Gottschlich [23] moderate Laskow [13] moderate Mbatha [14] moderate El-Zein [8] moderate Poli [16] low to moderate Vahabi [7] moderate to high Stanczuk [17] moderate Winer [4] moderate Chatzistamatiou [12] moderate B Requirements for quality assessment of articles included in the CASP checklist systematic review for randomized controlled trials comprised: (1) Did the study address a clearly focused issue? (2) Has the designation of patients for treatment been randomized?…”
Section: Types Of Sampling Methods Usedmentioning
confidence: 99%